Association among infant and young child feeding (IYCF) knowledge, practices, and vitamin A adequacy of complementary foods of first-time single mothers - Bandoy, Kyla Joy F.; Cariño, Annielle Reigh M.; Ham, Sung Min P.; Bayaga, Cecile Leah T. (Quezon City University of the Philippines Diliman, 2025)
Adequate nutrition during the first 1,000 days is crucial for optimal growth and development. Maternal knowledge of Infant and Young Child Feeding (IYCF) guidelines significantly influences complementary feeding (CF) practices, which impact the quality and nutrient content of an infant's diet. First-time single-mother households, balancing roles as both caregiver and breadwinner, may face challenges that limit diet diversity, which can increase risks of stunting and Vitamin A deficiency (VAD) in their children. This study investigated the association of IYCF knowledge and practices with Vitamin A adequacy in complementary foods among first-time single mothers with children aged 6-23 months. A cross-sectional descriptive-quantitative design was utilized, with purposive sampling to select the 23 participants from Quezon City. Maternal IYCF knowledge and CF practices indicators— Minimum Dietary Diversity (MDD) and Minimum Meal Frequency (MMF) were all assessed using a FAO questionnaire; whereas Vitamin A adequacy was measured through a two-day 24-hour food recall. Firth’s logistic regression and bootstrapping mediation analysis were used to determine the association of variables. Findings revealed that a significant relationship was found between IYCF knowledge and MDD, while no significant association was observed between: 1) knowledge and MMF; 2) practices and Vitamin A adequacy; and 3) knowledge and Vitamin A adequacy. This lack of association may stem from limited statistical power due to the small sample size. While knowledge supports dietary diversity, its link to meal frequency is less consistent, possibly reflecting financial constraints— underscoring the influence of socioeconomic factors on feeding practices. Further studies are recommended to expand recruitment coverage and collaborate with health centers to increase sample size. Exploring Vitamin A supplementation and biochemical assessments may improve understanding of VAD risk and its associations.
In partial fulfillment for the Degree of Bachelor of Science in Community Nutrition
Thesis
Keywords: Infants -- Nutrition -- Philippines; Single mothers -- Philippines; Vitamin A deficiency in children -- Philippines; Complementary feeding; Vitamin A; Maternal knowledge; Infant and young child feeding